Emerging diversity in extracellular vesicles and their roles in cancer - Sohal, Ikjot S.; Kasinski, Andrea L. (Frontiers in Oncology, 2023)
Extracellular vesicles have undergone a paradigm shift from being considered as ‘waste bags’ to being central mediators of cell-to-cell signaling in homeostasis and several pathologies including cancer. Their ubiquitous nature, ability to cross biological barriers, and dynamic regulation during changes in pathophysiological state of an individual not only makes them excellent biomarkers but also critical mediators of cancer progression. This review highlights the heterogeneity in extracellular vesicles by discussing emerging subtypes, such as migrasomes, mitovesicles, and exophers, as well as evolving components of extracellular vesicles such as the surface protein corona. The review provides a comprehensive overview of our current understanding of the role of these extracellular vesicles during different stages of cancer including cancer initiation, metabolic reprogramming, extracellular matrix remodeling, angiogenesis, immune modulation, therapy resistance, and metastasis, and highlights gaps in our current knowledge of extracellular vesicle biology in cancer. We further provide a perspective on extracellular vesicle-based cancer therapeutics and challenges associated with bringing them to the clinic.